Effect of septoria leaf blotch and its control with commercial fungicides, on arbuscular-mycorrhizal-fungal colonization, spore numbers, and morphotype diversity - Schalamuk, Santiago (2014)
Arbuscular-mycorrhizal internal structures (i.e. total root colonization, arbuscules, vesicles) and external structures (i.e. spore density), and Glomeromycota spore morphotypes, were evaluated in wheat severely infected with Mycosphaerella graminicola-the causal agent of Septoria leaf blotch. Plots in which the infection was controlled with a commercial fungicide at recommended field doses, were also examined. The commercial fungicide used was an admixture of trifloxistrobin and tebuconazole. No negative effects of the fungicide application on arbuscular-mycorrhizal fungi (AMF) were found. The M. graminicola fungicidal treatment actually favoured the formation of arbuscules and AMF spores, as there was a selective increase in the density of spores belonging to the glomoid morphotype. Arbuscular-mycorrhizal fungi have an absolute dependence on the carbon provided by the plant. A severe foliar disease leading to a diminished carbon supply to the roots would generate decreases in carbon availability. Such decreases would strongly affect mycorrhizal associations and development. Furthermore, the change in the green-leaf area produced by a severe foliar disease and/or a reversal of that condition through fungicide treatment could result in shifts in the composition of the AMF community so as to favour glomoid morphotypes. Glomoid species have been previously considered as r-strategists.